What Do We Mean When We Talk About Performance?: A Metacritical Overview of an Evolving Concept - Larson, Catherine (Latin American Theatre Review, 2011)
It is fair to state that performance is one of the most contested terms in our field,clearly evolving and emerging in the last few decades as one of the most significant terms ina wide range of academic disciplines and in society in general. This essay lays out many ofthe principal critical and theoretical concepts and debates related to performance—performativity,performance studies, performance art, etc.—to illustrate how the field and the lensthrough which we view it have changed and are continuing to change, as well as how thoseof us who study Latin American theater fit into the larger picture of examining the embodimentof meaning. This study of some of the main contributions to the discipline and to thecreation of the field of performance studies offers an overview of the concepts, scholarship,and bibliography that have helped shape the ways in which we talk about performance. (CL)